The role of palliative chemotherapy for terminally ill patients with advanced NSCLC. Issue 2 (22nd April 2013) - Yang, Dan; Qiu, Meng; Zou, Li‐qun; Zhang, Wei; Jiang, Yu; Zhang, Dong‐yu; Yan, Xi
Abstract: Background: To evaluate the conditions of palliative chemotherapy in terminally ill patients with advanced non‐small cell lung cancer (NSCLC), and to discuss the potential factors that affect the prognosis of these patients. Methods: All 205 terminally ill patients with advanced NSCLC, who died in our hospital during the period from 2006 to 2010, were included in the study. Basic information was collected and details for the treatment of patients, related to overall survival, were evaluated. Results: One hundred and fifty‐nine out of 205 patients (77.6%) were treated with palliative chemotherapy. Of these, 59.7% patients were treated with palliative chemotherapy in the last three months and 27.7% patients in the last one‐month, prior to their expiration, respectively. In addition, 22.0% of the 159 patients were treated with palliative chemotherapy for the first time in the last three months and 10.1% in the last month of their final days. We have shown that patients treated with palliative chemotherapy in their last three and final month had a shorter overall survival rate than those patients who were not treated with palliative chemotherapy. Conclusion: A large proportion of patients with advanced NSCLC received palliative chemotherapy near the end of their life. However, our results were not in favor of palliative chemotherapy in the last three or final month of life.